THE EFFECT OF STRIP STORY LEARNING MEDIA ON LEARNING OUTCOMES IN THE HISTORY OF ISLAMIC CULTURE SUBJECT - Aristiati, Fatimah (Nurul Jadid University, Paiton Probolinggo, East Java, 2023)
The purpose of this study was to see and test the extent of the influence of the use of strip story learning media on learning the history of Islamic culture in class V MI Al-Islamiyah Kotabumi. The method used in this research is a quantitative quasi-experimental method. The data were collected through the pre-test, post-test, and questionnaire. Data analysis used descriptive statistics and inferential statistics. The results showed that The incorporation of strip story media has yielded a positive impact on the learning of Islamic cultural history at MI Al-Islamiyah Kotabumi. This is evident through the substantial improvement in students' average scores from the pre-test to the post-test phase. Specifically, the average score for the pre-test in the experimental class was 63.33, while in the post-test, it soared to 86.67, denoting a noteworthy average score increase of 23.34 points. Moreover, the results of hypothesis testing reinforce the effectiveness of employing strip story media in History of Islamic Culture learning, as indicated by the significance value (sig.) of 0.001, which is lower than the 0.05 threshold. Consequently, it can be confidently concluded that the utilization of strip story media significantly enhances students' learning outcomes. The use of strip story media contributes to improving student learning outcomes in Islamic cultural history subjects so that it can be applied in madrasah